Price Squeezes in New Zealand Competition Law: Goodbye to the Efficient Component Pricing Rule and the Equally Efficient Competitor - Scott, Paul G (Victoria University of Wellington Law Review, 2022)
One of Professor Prebble’s many achievements is that he is a fellow of the Law and Economics Association of New Zealand. This achievement recognises his contribution to the economic analysis of law. The first field to which scholars applied economic analysis of law was competition law. This article examines a particularly contentious area of New Zealand’s competition law; viz the Efficient Component Pricing Rule and s 36 of the Commerce Act 1986. This rule first arose in Clear Communications Ltd’s dispute with Telecom Corp of New Zealand Ltd. The Privy Council endorsed charging on the basis of the rule – saying its use did not breach s 36. Many years later New Zealand’s Court of Appeal held Telecom’s use of it amounted to a breach of s 36 in the context of price squeeze litigation. This article examines how the Court of Appeal concluded this. It looks at the economics of price squeezes and the rationale behind the Efficient Component Pricing Rule. It discusses United States law on price squeezes and shows how that law is hostile to finding competition law liability for price squeezes. It outlines the New Zealand cases and analyses the reasoning of the cases – particularly the Court of Appeal price squeeze case. It concludes that in holding use of the rule was a breach of s 36 the Court has eliminated the equally efficient competitor standard test for monopolisation and interred the Efficient Component Pricing Rule. It also argues that proscribing price squeezes is worthwhile.